SB 1610 A BILL TO BE ENTITLED AN ACT RELATING TO FAIR EMPLOYMENT PRACTICES - SENATOR JONES (Tufts Archival Research Center, 2007)
Proposal for a bill prohibiting unfair employment hiring practices in the state of Florida. Strives to eliminate hiring discrimination based on participation in lawful activities during non-working hours.